BMP and TGFbeta pathways in human central chondrosarcoma: enhanced endoglin and Smad 1 signaling in high grade tumors - Boeuf, Stephane; Lehner, Burkhard; Richter, Wiltrud (BMC cancer, 2012)
As major regulators of normal chondrogenesis, the bone morphogenic protein (BMP) and transforming growth factor β (TGFB) signaling pathways may be involved in the development and progression of central chondrosarcoma. In order to uncover their possible implication, the aim of this study was to perform a systematic quantitative study of the expression of BMPs, TGFBs and their receptors and to assess activity of the corresponding pathways in central chondrosarcoma.
Gesehen am 10.10.2018